PERSEPSI SISWA DALAM MEMPELAJARI KOSA KATA BAHASA INGGRIS MELALUI GAME HANGAROO - Shofiyatul Najah; Yudhi Arifani (JELLT (Journal of English Language and Language Teaching), 2022)
Vocabulary learning for second and foreign language students is essential and needs attention during English language learning. That is because vocabulary is needed to master other English skills and communicate effectively in and outside the classroom. However, many elementary school students still lack vocabulary because they do not fit with the teaching method used. This study focuses on investigating the student perceptions of the implementation of the Hangaroo game in learning English vocabulary. The participant in this study is five students from elementary school in Thailand. The interview and observation were used to gather information and explanations regarding the student perceptions of learning English vocabulary through the Hangaroo game. For classification and summary purposes, a thematic analysis will be used to analyze the data in this research. The results showed that most students express their positive perception of vocabulary learning using the Hangaroo game. Accordingly, this research recommends that English teachers use the Hangaroo game to teach English vocabulary to students in the classroom.